EVO MORALES DAN PEMBENDUNGAN PENGARUH AMERIKA SERIKAT DI BOLIVIA - Wahid Musthafa (HI 16 UMY 092, 2016)
*92 ment Toward Socialism (MAS) won the presidential elections in Bolivia. His victory came after twenty years of neoliberal measures that increased poverty and fostered social unrest in the country. Throughout the 1990s and 2000s, social movements evolved as an important political actor in the country and their anti-neoliberal struggles led to the resignation of two presidents and a crack in the existing political system. Since Moralesâ€™ victory, Bolivia has promoted an alternative development model that is moving away from the basic principles of neoliberalism. The US has critized Morales for his close ties to Venezuelan President Hugo Chavez and Cuban President Fidel Castro. In the first of the wave of year-long presidential elections in Latin America to mark a significant shift in the western hemispheric balance of power between the United States and Brasil, bolivians voted into power Morales who is pledged to end Boliviaâ€™s depedence on the United States and to join the forces of regional autonomy and integration. Presenting him self as Washington â€œworst nightmareâ€ Morales stands on the far left of the current tendencies in Latin America to seek altenatives to Washington Neoliberal Economic Policies. An admirer of Cubaâ€™s Fidel Castro and Venezuelaâ€™s Hugo Chavez, Morales based his campaign on promises to wrest control of the gas reserves and the hydrocarbons industry from the mutinational energy corporation that had invested in bolivia during its pro-US administrations of the past 20 years. Morales also pledged to decriminalize the culvitation of the coca leaf for its traditional use as a mild stimulant and medicinal tea, and to fight the cocaine trade, promising to end cooperation with Washingtonâ€™s Programs to eliminate the crops. Morales wrapped up his proposals in an ideology that attacked the neoliberal mareket model and offeredin its place a vision of cooperative socialism and regional integration similar to Chavez â€œBolivarian Revolutionâ€ Keywords: Socialism, Social Movement, Latin America, Bolivia, Evo Morales